Expression Profile of microRNAs Regulating Proliferation and Differentiation in Mouse Adult Cardiac Stem Cells - Brás-Rosário, Luis (2015)
The identification of cardiac cells with stem cell properties changed the paradigm of the heart as a post mitotic organ. These cells proliferate and differentiate into cardiomyocytes, endothelial and vascular smooth muscle cells, providing for cardiac cell homeostasis and regeneration. microRNAs are master switches controlling proliferation and differentiation, in particular regulating stem cell biology and cardiac development. Modulation of microRNAs -regulated gene expression networks holds the potential to control cell fate and proliferation, with predictable biotechnologic and therapeutic applications. To obtain insights into the regulatory networks active in cardiac stem cells, we characterized the expression profile of 95 microRNAs with reported functions in stem cell and tissue differentiation in mouse cardiac stem cells, and compared it to that of mouse embryonic heart and mesenchymal stem cells. The most highly expressed microRNAs identified in cardiac stem cells are known to target key genes involved in the control of cell proliferation and adhesion, vascular function and cardiomyocyte differentiation. We report a subset of differentially expressed microRNAs that are proposed to act as regulators of differentiation and proliferation of adult cardiac stem cells, providing novel insights into active gene expression networks regulating their biological properties.